Addison's Disease and Pituitary Enlargement. (June 2015) - Winters, Stephen J.; Vitaz, Todd; Nowacki, Michael R.; Craddock, Durrett C.; Silverman, Craig
Abstract : Abstract: A 60-year-old man with Addison's disease, primary hypothyroidism and type 2 diabetes mellitus who was treated with stable doses of hydrocortisone and fludrocortisone developed increasing skin pigmentation and a bitemporal hemianopia. The plasma ACTH level was 14, 464 pg/mL, and an invasive pituitary macroadenoma with suprasellar extension was found on magnetic resonance imaging leading to transnasal-transsphenoidal adenomectomy. The tumor demonstrated features of an eosinophilic adenoma and stained uniformly for ACTH. Residual tumor was treated with stereotactic radiotherapy. This case and the 13 cases published previously indicate that primary adrenal failure may predispose to corticotroph hyperplasia, and in some patients to the development of an invasive corticotroph adenoma. The ACTH level should be measured, and a pituitary magnetic resonance imaging is indicated when skin pigmentation increases in a patient with primary adrenal failure who is receiving customary treatment with glucocorticoids and mineralocorticoids.